501 VISTA regulates the differentiation and suppressive function of myeloid-derived suppressor cells. (9th November 2020) - Dong, Juan; Gilmore, Cassandra; Ta, Hieu; Zhang, Keman; Stone, Sarah; Wang, Li
Abstract : Background: V-domain immunoglobulin suppressor of T cell activation (VISTA) is a B7 family inhibitory immune checkpoint protein and is highly expressed on myeloid cells and T cells. 1 VISTA acts as both an inhibitory ligand when expressed on antigen-presenting cells and a receptor when expressed on T cells. Our recent study has shown that VISTA is a myeloid cell-specific immune checkpoint and that blocking VISTA can reprogram suppressive myeloid cells and promote a T cell-stimulatory tumor microenvironment. 2 In this study, we further demonstrate that VISTA blockade directly alters the differentiation and the suppressive function of myeloid-derived suppressor cells (MDSC). Methods: Flow cytometry was performed to examine VISTA expression on MDSCs in multiple murine tumor models including the B16BL6 melanoma model, MC38 colon cancer model, and the KPC pancreatic cancer models. To examine the role of VISTA in controlling the differentiation and suppressive function of MDSCs, we cultured wild type (WT) and VISTA.KO bone marrow progenitor cells with GM-CSF and IL-6 to induce BM -derived MDSCs. Results: Our preliminary results show that VISTA is highly expressed on M-MDSCs in B16BL6, MC38 and KPC tumors. In BM-derived MDSCs, VISTA deletion significantly altered the signaling pathways and the differentiation of MDSCs. Multiple inflammatory signaling pathways were downregulated in VISTA KO MDSCs, resulting in decreased production of cytokines such as IL1 and chemokines such as CCL2/4/9, as well as significantly impaired their ability to suppress the activation of CD8+ T cells. The loss of suppressive function in VISTA KO MDSCs is correlated with significantly reduced expression of iNOS. To validate the results from BM-MDSCs, we sorted CD11b+CD11c-Ly6C+Ly6G- M-MDSCs and CD11b+CD11c-Ly6G+ G-MDSCs from B16BL6 tumor tissues and tested the ability of a VISTA-blocking mAb to reverse the suppressive effects of tumor-derived MDSCs. Our results show that blocking VISTA impaired the suppressive function of tumor-derived M-MDSC but not G-MDSCs. Conclusions: Taken together, these results demonstrate a crucial role of VISTA in regulating the differentiation and function of MDSCs, and that blocking VISTA abolishes MDSC-mediated T cell suppression, thereby boosting. Ethics Approval: All in vivo studies were reviewed and approved by Institutional Animal Care and Use Committee (Approval number 2019-2142). References: Xu W, Hire T, Malarkannan, S. et al. The structure, expression, and multifaceted role of immune-checkpoint protein VISTA as a critical regulator of anti-tumor immunity, autoimmunity, and inflammation. Cell Mol Immunol 2018;15:438–446. Xu W, Dong J, Zheng Y, et al. Immune-checkpoint protein VISTA regulates antitumor immunity by controlling myeloid cell-mediated inflammation and immunosuppression. Cancer Immunol Res 2019;7:1497–510.